Analisis Keterampilan Menulis Paragraf Siswa Kelas Sepuluh di SMA Negeri 1 Kuok - Wira Elvina (Culture education and technology research (Cetera), 2025)
This study aims to analyze paragraph writing skills of tenth-grade students at SMA Negeri 1 Kuok. It applied a qualitative approach using writing tests and documentation as instruments. The sample consisted of 20 students selected by purposive sampling. Assessment was based on five writing components: content, organization, vocabulary, grammar, and mechanics. The findings showed that the average student score was 78.2, which falls into the "good" category. Grammar and vocabulary were found to be the weakest areas. This study recommends more writing practice and grammar reinforcement to enhance students’ writing performances.